Effects of hydrogen sulfide on storage quality, water mobility and cell wall metabolism of strawberry fruit - Zhi, Huanhuan; Liu, Qiqi; Dong, Yu (International Journal of Agricultural and Biological Engineering, 2018)
The effects of hydrogen sulfide (H2S) on storage quality, cellular water distribution, and cell wall metabolism of strawberry fruit after subjected to shelf or cold storage were investigated. Fruit were fumigated with a range of aqueous NaHS solution (0.4-3.2 mmol/L), then stored at 20°C for 3 d or 0°C for 9 d. H2S-treated fruit significantly maintained higher fruit firmness (FF) and titratable acidity (TA) as well as lower decay compared to the control fruit. Furthermore, H2S inhibited the loss in extractable juice (EJ) and improved storage quality that not only resulted from the suppressing of respiration rate, but also from the modification of water mobility and cell wall metabolism. High FF and EJ in H2S-treated fruit were closely associated with lower exchanges of free water between vacuole and cytoplasm/free space or cell wall, water-soluble polysaccharides (WSP), and activities of cell wall-modifying enzymes. Therefore, a potential benefit of H2S on retarding softening was that the H2S can reinforce the hydrogen bonding in polysaccharides and reduce activities of cell wall-modifying enzymes, causing a stabilization of cell wall structure. Although approval of the use of H2S on foods has not yet been granted, an alternative reducing agent gas based on H2S tended to be more effective in improving strawberry quality. Keywords: hydrogen sulfide, strawberry, softening, water mobility, cell wall metabolism DOI: 10.25165/j.ijabe.20181106.4074 Citation: Zhi H H, Liu Q Q, Dong Y. Effects of hydrogen sulfide on storage quality, water mobility and cell wall metabolism of strawberry fruit. Int J Agric & Biol Eng, 2018; 11(6): 201–207.